Comparación de Dispositivos para la Adquisición de Señales de Acelerometría en Extremidades Superiores para la Caracterización del Temblor Parkinsoniano - Salgado López, Álvaro; Carmona Almazan, Andres; Dorantes Mendez, Guadalupe; Mejia Rodriguez, Aldo Rodrigo (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Tremor is the most common motor disorder of Parkinson’s disease (PD). Since accelerometry analysis can help determining the frequency, amplitude, and occurrence of tremor. We compared accelerometry (ACC) acquisitions from two devices to assess Parkinsonian Tremor in upper limbs. The first one, is designed in this work and it is based on an ACC wrist movement acquisition, the second one was designed previously, which is placed on the finger for ACC acquisition. The wrist band device designed in this work is a prototype made with easy access and low-cost components. ACC signals were acquired from 3 healthy volunteers placing our devices on wrist and on the index finger while performing specific maneuvers that enhance the presence of tremor in the upper limbs. The results suggest that ACC signals from both devices are comparable, considering a correlation coefficient of 0.9953, despite the ACC sensors were placed in different sections of the upper limbs.